2023
DOI: 10.3390/jcm12227116
|View full text |Cite
|
Sign up to set email alerts
|

Serum-Creatinine-to-Cystatin C-to-Waist-Circumference Ratios as an Indicator of Severe Airflow Limitation in Older Adults

Jinxuan Li,
Qi Sun,
Hongguang Zhang
et al.

Abstract: Background: This study aimed to investigate the association between the serum-creatinine-to-cystatin C-to-waist-circumference (CCR/WC) ratio with lung function and severe airflow limitation (SAL). Methods: The data were derived from the China Health and Retirement Longitudinal Study. Peak expiratory flow (PEF) was used as a measure of lung function parameter. Logistic and linear regression were utilized separately to evaluate the relationship between the CCR/WC ratio with PEF and SAL in baseline. Restricted cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Additionally, sarcopenia-induced respiratory muscle weakness significantly impacts peak respiratory flow rates. Studies have shown a longitudinal link between decreased PEF and sarcopenia ( 35 , 36 ). Moreover, low physical activity and impaired respiratory function due to sarcopenia exacerbate fatigue, further increasing frailty risk and perpetuating a vicious cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, sarcopenia-induced respiratory muscle weakness significantly impacts peak respiratory flow rates. Studies have shown a longitudinal link between decreased PEF and sarcopenia ( 35 , 36 ). Moreover, low physical activity and impaired respiratory function due to sarcopenia exacerbate fatigue, further increasing frailty risk and perpetuating a vicious cycle.…”
Section: Discussionmentioning
confidence: 99%